Komunikasi Qur’ani bagi Penanganan Anak pada Pornografi di Media Sosial - Sugiarto (El Madani : Jurnal Dakwah dan Komunikasi Islam, 2022)
The purpose of this study is to analyze and explore the communication of qur'ani implemented by parents towards children in dealing with the problem of pornography on social media. Because, so many cases occur in children due to exposure to pornography on social media, both reported by authoritative parties and based on literature and research results, both in Indonesia and abroad. The research uses virtual communication theory, pornography concepts, and Qur'ani communication that uses a persuasive model (QS.4: 63), full of wisdom (QS.2: 235), humanist (QS.17: 23), weighty (QS.73: 5), contextually (QS.4: 9), the best speech or narrative (QS.41:33), polite (QS.20:44) logical and easy to understand (QS.17:28). The research method used is the maudhu'i method (thematic interpretation), by conducting an inventory of the verses discussed then looking for interpretations from the mufassir and then the author gives an opinion on the verses discussed. The findings in this study support the opinions of Nashih 'Ulwan (2019), Kastleman (2016), and Mulyadi (2019) which states that pornography is not only a matter of one's freedom of expression, but also concerns many interests that are very harmful to the wider interests, especially if pornography is consumed by children. In addition, qur'ani communication has an approach, method, and model that is comprehensive, holistic, and effective. which can be implemented by parents in handling children in preventing the tendency of children to engage in pornographic content on social media. In addition, this study rejects the opinion of Wendy McElroy (1997) which states that a person has the right to his body and also has the right to express, display and even distribute it.